Management of neonatal hyperbilirubinemia: Pediatricians' practices and educational needs - Ostfeld Barbara; Birchwood Gillian; Mehta Rajeev; Petrova Anna; Hegyi Thomas (BMC, 2006)
Abstract Background Early detection and treatment of neonatal hyperbilirubinemia is important in the prevention of bilirubin-induced encephalopathy. In this study, we evaluated the New Jersey pediatricians' practices and beliefs regarding the management of neonatal hyperbilirubinemia and their compliance with the recommendations made by the American Academy of Pediatrics (AAP) in 1994. Methods A survey questionnaire was mailed to a random sample of 800 pediatricians selected from a list of 1623 New Jersey Fellows of the AAP initially in October 2003 and then in February 2004 for the non-respondents. In addition to the physicians' demographic characteristics, the questionnaire addressed various aspects of neonatal hyperbilirubinemia management including the diagnosis, treatment, and follow up as well as the pediatricians' beliefs regarding the significance of risk factors in the development of severe hyperbilirubinemia. Results The adjusted response rate of 49.1% (n = 356) was calculated from the 725 eligible respondents. Overall, the practicing pediatricians reported high utilization (77.9%) of the cephalocaudal progression of jaundice and low utilization (16.1%) of transcutaneous bilirubinometry for the quantification of the severity of jaundice. Most of the respondents (87.4%) identified jaundice as an indicator for serum bilirubin (TSB) testing prior to the neonate's discharge from hospital, whereas post-discharge, only 57.7% felt that a TSB was indicated (P < 0.01). If the neonate's age was under 72 hours, less than one-third of the respondents reported initiation of phototherapy at TSB levels lower than the treatment parameters recommended by the AAP in 1994, whereas if the infant was more than 72 hours old, almost 60% were initiating phototherapy at TSB lower than the 1994 AAP guidelines. Most respondents did not regard neonatal jaundice noted after discharge and gestational ages 37-38 weeks as being significant in the development of severe hyperbilirubinemia. However, the majority did recognize the importance of jaundice presenting within the first 24 hours and Rh/ABO incompatibility. Conclusion The pediatricians' practices regarding the low utilization of laboratory diagnosis for the quantification of jaundice after discharge and underestimation of risk factors that contribute to the development of severe hyperbilirubinemia are associated with initiation of phototherapy at lower than AAP recommended treatment parameters and recognition of neonatal hyperbilirubinemia as an important public health concern.